Comparison of Platelet-to-High-Density Lipoprotein Cholesterol Ratio between Patients with Ischemic Stroke and Healthy Controls - Debie Anggraini; Yuri Haiga; Vina Tri Septiana (CV. AKBAR PUTRA MANDIRI, 2026)
Background: Ischemic stroke is a major cerebrovascular disorder involving complex interactions between thrombosis, platelet activation, endothelial dysfunction, and lipid abnormalities. The platelet-to-high-density lipoprotein cholesterol ratio (PHR) is a simple composite index combining platelet count and HDL-C, potentially reflecting the interaction between thrombotic and lipid-related vascular processes. However, evidence directly comparing PHR between patients with ischemic stroke and healthy individuals remains limited. Objective: To compare the platelet-to-high-density lipoprotein cholesterol ratio between patients with ischemic stroke and healthy controls. Methods: This analytical observational study used a case-control design and was conducted at Siti Rahmah Hospital, Padang, Indonesia, using data from 2022–2024. The study included 21 patients with ischemic stroke confirmed by brain computed tomography and 21 healthy controls. Platelet count and HDL-C measurements were obtained from laboratory records. For stroke patients, laboratory measurements obtained on the first day of hospitalization were used. PHR was calculated as platelet count (×10³/µL) divided by HDL-C (mg/dL). Differences between groups were analyzed using the Mann–Whitney U test for non-normally distributed continuous variables. A p value <0.05 was considered statistically significant. Results: The median PHR was significantly higher in patients with ischemic stroke than in healthy controls (5.80 [IQR, 5.27–7.56] vs. 3.61 [IQR, 3.13–5.00], p = 0.001). HDL-C concentrations were significantly lower in the ischemic stroke group (40 [36–51] vs. 59 [45–76] mg/dL, p < 0.001). In contrast, platelet count did not differ significantly between the groups (285 [227–318] vs. 245 [192–289] ×10³/µL, p = 0.119). Conclusion: PHR was significantly higher in patients with ischemic stroke than in healthy controls, with the difference appearing to be driven predominantly by lower HDL-C rather than by a significant difference in platelet count. PHR may represent a simple laboratory index reflecting the interaction between platelet-related and lipid-related processes in ischemic stroke. Further studies with larger and well-matched populations are needed to validate these findings.